Penerapan Persyaratan Umum Instalasi Listrik 2011 Pada Instalasi Listrik Bangunan Gedung - Tanjung, Abrar; Arlenny, Arlenny; Setiawan, David; Eteruddin, Hamzah; Fauzi, Muhammad Ridha (Jurnal Pengabdian UntukMu NegeRI, 2023)
The installation of lighting does not only cover the problem of lighting but includes the installation of equipment (fans, electric motors, water pumps, air conditioners, etc.) PT. Sumatera Riang Lestari is a company engaged in the industrial sector that does not know and understand how to properly install and operate electrical equipment. Based on the results of identifying problems with partners, identifying problems with partners PT. Sumatra Riang Lestari which is being faced by activity partners. In the operation of electrical installation equipment, it often experiences damage, for example there is a voltage drop, damage to equipment occurs and power outages occur. The results of the discussion partners know and master Basic Knowledge of Electrical Installation after socialization 92%, General Requirements for Electrical Installation (PUIL) 2011 by 88%, Electricity Standardization (SNI) by 96%, Use and Operation of Electrical Equipment according to Electricity Standards (SNI) according to Electricity Standards (SNI) of 88%, Electrical Installation Materials and Components of 96%